Active Surveillance of the Implantable Cardioverter-Defibrillator Registry for Defibrillator Lead Failures. Issue 4 (April 2020) - Resnic, Frederic S.; Majithia, Arjun; Dhruva, Sanket S.; Ssemaganda, Henry; Robbins, Susan; Marinac-Dabic, Danica; Hewitt, Kathleen; Ohno-Machado, Lucila; Reynolds, Matthew R.; Matheny, Michael E.
Abstract : Background: Several defibrillator leads have been recalled due to early lead failure leading to significant patient harm. Confirming the safety of contemporary defibrillator leads is essential to optimizing treatment for patients receiving implantable cardioverter-defibrillators (ICDs). We therefore sought to assess the comparative long-term safety of the 4 most commonly implanted ICD leads within the National Cardiovascular Data Registry ICD Registry. Methods and Results: A propensity-matched survival analysis of the ICD Registry was performed evaluating 4 contemporary ICD leads in patients receiving an ICD system for the first time. All patients in the ICD Registry aged ≥18 years who underwent an implant of an ICD between April 1, 2011 and March 31, 2016 were included. Monitoring of safety began with ICD implant and continued up to 5 years. A meaningful difference in ICD failure rate was defined as twice (or more) the lead failure rate observed in the propensity-matched comparator patients. Among the 374 132 patients who received a new ICD implant, no safety alerts were triggered for the primary safety end point of lead failure for any of the high energy leads studied. Estimated rates of freedom from lead failure at 5 years ranged from 97.7% to 98.9% for the 4 high-energy leads of interest. Conclusions: Though limited by incomplete long-term outcomes ascertainment, active surveillance of the ICD Registry suggests that there were no meaningful differences in the rate of ICD high-energy lead survival for the 4 most commonly used high-energy ICD leads. Abstract : Supplemental Digital Content is available in the text.